Bigge, Ägypten - Schäfer, Bernadeta (e-Forschungsberichte des DAI, 2017)
The field work of 2015/16 on Bigge, the little island between the two dams of Aswan south of the Philae temple complex, focussed on the examination of two Nubian villages: Balle and Bigge. Both villages date back between 1912 and 1933 and were left about 25 years ago and have since then been prone to massive decay through climatic circumstances as well as vandalism and illicit digging. The villages’ vernacular architecture consists of ca. 30 houses. In addition, pathways and commonly used spaces, cultivable land and two cemeteries in the island’s centre can still easily be traced.